Comparing the Effectiveness of Expansionary Monetary vs. Fiscal Policies in Boosting GDP in Cambodia - Mong, Mara (Journal of Ecohumanism, 2025)
Four indicators were incorporated into a system of equations using a structural vector autoregressive (SVAR) model, specifically gross domestic product (GDP), consumer price index (CPI), money supply (M2), and government expenditure (G), to assess the effectiveness of macroeconomic policies, including both monetary and fiscal policies, in Cambodia. The empirical results indicated that the growth of the money supply produced a positive impact on economic growth, peaking in the second quarter before gradually converging to equilibrium by the fourth quarter. Conversely, government expenditure and the inflation rate initially exerted a negative impact on economic growth during the first and second quarters, followed by a positive effect starting in the second quarter, ultimately converging to equilibrium by the fourth quarter.